Autorki - Mrozowski, Janusz (Poland ; France : Filmogène Janusz Mrozowski, 2014)
Four Polish female prisoners are taken in a police convoy to the premiere of a play about their lives, which they wrote. On their way to the theater the authors worry how the audience will take their tantalizing and often shocking stories. Meanwhile, the play's director and actors worry if the women will endorse their sometimes controversial interpretation of the script.
Verzio Film Festival Submission
Keywords: Documentary films